Spatiotemporal evolution of scouring and silting in Made Island port channel (2015–2023) - Wang, Qiang; Wang, Guanghui; Jiang, Hongwei; Song, Hailong; Ma, Dianguang; Duan, Yu (Frontiers in Marine Science, 2025)
This paper, based on channel topographic survey data from 2015 to 2023, analyzes the scouring and silting evolution characteristics of the Made Island port channel, port basin, outer anchorage, and empty ship anchorage. By conducting a quantitative analysis of water depth variations and scouring and silting phenomena across different years, this paper investigates the effects of water flow, topographic changes, and human dredging activities on the topographic evolution of the port area. The study utilizes bathymetric survey data collected at two-year intervals using the MV SEA PRINCESS survey vessel, equipped with a Positioning, Motion and Heading Unit, Bathymetric Equipment for Sounding, Sound Velocity Profiler, Single Beam Echosounder, and Transducers. The monitoring methodology involved interpolating and subtracting multi-year bathymetric data to assess sediment transport dynamics. The results indicate that the Made Island port channel exhibits a dynamic alternation of scouring and silting, with significant sediment accumulation in shallow areas, especially after dredging operations. Notably, the outer anchorage experiences the highest silting rates in years with increased sediment supply, whereas the port basin generally maintains deeper water levels, ensuring its functionality despite localized siltation. The empty ship anchorage shows strong correlations between water flow speed variations and sediment deposition, leading to navigational constraints in certain conditions. The findings indicate that the scouring and silting phenomena in the port area are the result of multiple interacting factors. The paper recommends regular topographic monitoring and the implementation of necessary dredging and maintenance measures to ensure the efficient operation and navigational safety of the port.